Caminhos do sertão em morte e vida Severina: diálogo entre a geografia e a literatura - Ramos, Ana Carolina Robles de Cara (2016)
This dissertation describes, from a geographic view, aspects of the perception of geographic space concept in the poem Morte e vida severina, written by João Cabral de Melo Neto in 1956. The work concerned is one of the most meaningful of our literature. A saga that shows the leaving of the habitants from Sertão Nordestino, interior of the country, to the Zona da Mata, fleeing from death caused by the drought and looking for a humid and fertile life. On this travel, Severino faces the physical geographic space, with its natural aspects, like the semiarid weather, the caatinga, intermittent rivers and a landscape of mountains and plateaus, and also with a space marked by anthropic alteration, with cities, cane fields, stilt houses on swamps. The Capibaribe River is the course of the main character, which migrates from the inner country to Recife, promoting the comprehension of the relation of man and nature. In this writing, the poetry built is translated on Severino’s experience with nature, aspect which can be approach on Geography classes for the construction of geographic space concept, main category of geographic science. The reflections presented on this dissertation are structured by the viewpoint of cultural geography and by the complex thought. It is a study of bibliographic review in which we have as theoretical reference writers as Eduardo Marandola Júnior, Janaína Marandola, Ana Lúcia Gratão, Roberto Lobato Corrêa, Milton Santos and Edgar Morin. These thinkers’ works reinforced the interest upon studying literary works, analyzing it from a geographic point of view. This relation appears as an idea of valorization and recovering of categories from Geography which are described on literary works, and which displays how human life is perceived and relates with geographic space. As result, the present work demonstrates the way by which “poética cabralina” allows the interaction between Geography and Literature to the comprehension of geographic space concept on classes.